Analysis of the evidence about the efficacy and safety of the CYD-TDV dengue vaccine and its potential licensing and implementation within the Mexican Universal Vaccination Program - Mauricio Hernández-Ávila; José Ignacio Santos-Preciado (Instituto Nacional de Salud Pública, 2016)
Dengue is a major global public health problem which affects Latin America and Mexico. The prevention and control measures focusing on epidemiological surveillance and vector control have been partially effective as well as costly; thus, the development of a vaccine against dengue has created great expectations among the health authorities and scientific communities worldwide. The CYD-TDV dengue vaccine produced by Sanofi-Pasteur is the only dengue vaccine evaluated in phase III controlled clinical trials. However, despite the significant contribution to the development of a vaccine against dengue, the three phase III clinical studies of CYD-TDV and the meta-analysis of the long-term follow-up of those studies have provided evidence that this vaccine exhibited partial efficacy to protect against virologically confirmed dengue and lead to four considerations: a) adequate vaccine efficacy against infection by dengue viruses (DENV) 3 and 4, a lower vaccine efficacy against DENV 1, and null protection against infection by DENV 2; b) decreased vaccine efficacy in dengue seronegative individuals at the time of the initial vaccination; c) 83 and 90% protection against hospitalizations and severe forms of dengue, respectively, at 25 months follow-up; and d) increased hospitalization for dengue in the vaccinated group, in children under nine years of age at the time of vaccination, detected since the third year of follow-up. The benefit of CYD-TDV vaccine consists in protection against infection by DENV 3 and 4, as well as protection from hospitalizations and severe cases in individuals over nine years who have had a previous dengue infection, working mainly as a booster. In this review we identified elements of the efficacy and safety of this vaccine that must be taken into account in the licensing process and potential inclusion in the national vaccination program of Mexico. The available scientific evidence on the CYD-TDV vaccine shows merits but also leads to relevant questions that should be answered in order to properly assess the safety profile of the product and the target populations for potential benefit. In this regard we consider it would be informative to complete the 6-year follow-up after starting vaccination, according to the company's own studies protocol, as recommended by the World Health Organization. As with any new vaccine, the potential licensing and implementation of use of CYD-TDV in the Mexican vaccination program requires a clear definition of the balance between the expected benefits and risks. Particularly in the face of a vaccine with variable efficacy and the presence of some signs of risk, in the probable case of licencing, this must be followed by the development of detailed protocols in order to immediately identify any risks or health events associated with the vaccination.   DOI: http://dx.doi.org/10.21149/spm.v58i1.7956